PEMBENTUKAN SIKAP KEAGAMAAN PESERTA DIDIK MELALUI PENERAPAN METODE TAJRIBI DI SMA NEGRI 6 BULUKUMBA - Hidayat, Rahmat; Muzakkir; Muhammad Rusmin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2024)
This study aims to describe the implementation of the tajribi method in shaping the religious attitudes of students at SMA Negeri 6 Bulukumba. The research focuses on identifying the challenges, implementing the process, and measuring its outcomes. Employing a qualitative-descriptive approach, primary data were collected through field observations and interviews with relevant respondents. The data were then analyzed using data reduction, presentation, and conclusion-drawing techniques. The findings indicate that implementing the tajribi method involves several key steps. First, teachers act as role models by demonstrating polite behavior and modest attire while fostering students’ cooperation, discipline, and obedience to support character building. Second, students are habituated to perform congregational prayers and recite the Qur'an to achieve indicators of religious attitudes. Third, students are encouraged to practice greeting others as a form of social interaction aligned with Islamic teachings. Fourth, polite speech is emphasized as part of character development. The application of this method has shown significant improvements in students' religious attitudes, including increased discipline, punctuality, memorization of the 30th juz of the Qur'an, and active participation in congregational prayers. This study contributes to the development of experience-based approaches in religious education and recommends integrating the tajribi method as a primary strategy for fostering religious attitudes to achieve sustainable outcomes